2009
DOI: 10.1088/0004-637x/705/1/l53
|View full text |Cite
|
Sign up to set email alerts
|

Dust Emission From a Parsec-Scale Structure in the Seyfert 1 Nucleus of NGC 4151

Abstract: We report mid-IR interferometric measurements with ∼ 10 mas resolution, which resolve the warm (T = 285 +25 −50 K) thermal emission at the center of NGC 4151. Using pairs of VLT 8.2 m telescopes with MIDI and by comparing the data to a Gaussian model, we determined the diameter of the dust emission region, albeit only along one position angle, to be (2.0 ± 0.4) pc (FWHM). This is the first size and temperature estimate for the nuclear warm dust distribution in a Seyfert 1 galaxy. The parameters found are compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 26 publications
11
67
0
Order By: Relevance
“…The most promising tool for this task is IR interferometry, which was already successfully used for a number of nearby objects (Swain et al 2003;Wittkowski et al 2004;Weigelt et al 2004;Jaffe et al 2004;Poncelet et al 2006;Meisenheimer et al 2007;Tristram et al 2007Tristram et al , 2009Beckert et al 2008;Raban et al 2009;Burtscher et al 2009;Kishimoto et al 2009b). However, except for reconstructed images of NGC 1068 obtained from Speckle interferometry (Weigelt et al 2004), long-baseline interferometry usually provides spatial information coded as Fourier space observables, i.e.…”
Section: Interferometry Of Dust Torimentioning
confidence: 99%
“…The most promising tool for this task is IR interferometry, which was already successfully used for a number of nearby objects (Swain et al 2003;Wittkowski et al 2004;Weigelt et al 2004;Jaffe et al 2004;Poncelet et al 2006;Meisenheimer et al 2007;Tristram et al 2007Tristram et al , 2009Beckert et al 2008;Raban et al 2009;Burtscher et al 2009;Kishimoto et al 2009b). However, except for reconstructed images of NGC 1068 obtained from Speckle interferometry (Weigelt et al 2004), long-baseline interferometry usually provides spatial information coded as Fourier space observables, i.e.…”
Section: Interferometry Of Dust Torimentioning
confidence: 99%
“…In the midinfrared, Jaffe et al (2004) spatially resolved a parsec-sized torus-shaped distribution of dust grains in the same galaxy, where a small hot structure is embedded in a colder (320 K) dusty cocoon extending up to 3.4 pc in diameter. Further fluxlimited interferometric studies of nearby quasars, using the MIDinfrared Interferometric instrument (MIDI) at the Very Large Telescope Interferometer (VLTI; see, e.g., Tristram et al 2007;Burtscher et al 2009Burtscher et al , 2013Tristram et al 2014) or the Keck interferometer (Swain et al 2003;Kishimoto et al 2009a), definitively confirmed the existence of the dusty torus, if with large differences within the sample.…”
Section: Introductionmentioning
confidence: 98%
“…early results on Seyfert 2 galaxies by Jaffe et al 2004; radio galaxy, Meisenheimer et al 2007; type 1 AGNs, Beckert et al 2008;Kishimoto et al 2009b;Burtscher et al 2009; snapshot survey, Tristram et al 2009). In the near-IR, after the very early results for the brightest Seyfert 1 galaxy NGC 4151 (Swain et al 2003) and Seyfert 2 galaxy NGC 1068 (Wittkowski et al 2004), long-baseline interferometry has now started to explore the innermost dusty structure extensively at milli-arcsec (mas) resolution (Kishimoto et al 2009a, hereafter Paper I; Pott et al 2010).…”
Section: Introductionmentioning
confidence: 99%